1980
DOI: 10.2466/pr0.1980.47.3f.1245
|View full text |Cite
|
Sign up to set email alerts
|

Token Reinforcement Procedures for Reduction of Cigarette Smoking in a Psychiatric Outpatient Clinic

Abstract: A token-economy procedure was effective in significantly reducing the number of cigarettes smoked by a group of 30 psychiatric outpatients attending a day-treatment center at a state hospital. Treatment gains of the group obtained after a 4-wk. intervention were maintained during a 1-yr. follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Research employing reduction‐focused interventions has shown promise at reducing smoking or exposure to tobacco toxicants among those with schizophrenia (Barmann et al. 1980; Dawley et al.…”
Section: Empirical Evidence Supporting Smoking Reduction For Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research employing reduction‐focused interventions has shown promise at reducing smoking or exposure to tobacco toxicants among those with schizophrenia (Barmann et al. 1980; Dawley et al.…”
Section: Empirical Evidence Supporting Smoking Reduction For Patientsmentioning
confidence: 99%
“…positive reinforcement) have also been used to reduce smoking among patients with schizophrenia. Barmann et al. (1980) were one of the first groups to test the hypothesis that smoking could be reduced within a day‐treatment program in a psychiatric outpatient clinic.…”
Section: Empirical Evidence Supporting Smoking Reduction For Patientsmentioning
confidence: 99%